Nager Syndrome: A Case Report - Ju-Li Lin (Pediatrics and Neonatology)
Nager syndrome (preaxial acrofacial dysostosis) is rare and mostly sporadic. We present a case of Nager syndrome in Taiwan. Craniofacial findings included micrognathia, malar hypoplasia, downslanting palpebral fissures, cleft palate, and ear anomalies. Radial defects consisted of hypoplastic thumb, short forearm, and proximal radioulnar synostosis. Patent ductus arteriosus, atrial septal defect, lower limb deformities, and uncommon flat nasal bridge were noted. Nasal endotube passing through a narrowing oropharynx region or oral airway is life-saving before tracheostomy is performed on patients with Nager syndrome and restricted jaw opening and glossoptosis.